ENSURING EFFICIENCY IN TAX AUDIT: TURKEY AS A CASE STUDY - DİNÇER , Ekrem and ARSLAN, Ahmet (SSD Journal, 2021)
It is obvious that the tax, which is the income obtained by the state based on its sovereign power, is important in terms of financing public expenditures in developing countries. However, the efficiency of the tax audit, which we come across while investigating the compliance of the tax in question with the necessary legal regulations, is equally important. In this study, tax audit in our country, the effectiveness and efficiency of recent changes in the tax audit, and tax audit performed in other countries will be evaluated by comparison.